Design, Synthesis, Molecular Docking, and Antibacterial Evaluation of Some Novel Flouroquinolone Derivatives as Potent Antibacterial Agent - Mehul M. Patel; Laxman J. Patel (The Scientific World Journal)
Objective. Quinolone moiety is an important class of nitrogen containing heterocycles widely used as key building blocks for medicinal agents. It exhibits a wide spectrum of pharmacophores and has bactericidal, antiviral, antimalarial, and anticancer activities. In view of the reported antimicrobial activity of various fluoroquinolones, the importance of the C-7 substituents is that they exhibit potent antimicrobial activities. Our objective was to synthesize newer quinolone analogues with increasing bulk at C-7 position of the main 6-fluoroquinolone scaffold to produce the target compounds which have potent antimicrobial activity. Methods. A novel series of 1-ethyl-6-fluoro-4-oxo-7-{4-[2-(4-substituted phenyl)-2-(substituted)-ethyl]-1-piperazinyl}-1,4-dihydroquinoline-3-carboxylic acid derivatives were synthesized. To understand the interaction of binding sites with bacterial protein receptor, the docking study was performed using topoisomerase II DNA gyrase enzymes (PDB ID: 2XCT) by Schrodinger’s Maestro program. In vitro antibacterial activity of the synthesized compounds was studied and the MIC value was calculated by the broth dilution method. Results. Among all the synthesized compounds, some compounds showed potent antimicrobial activity. The compound 8g exhibited good antibacterial activity. Conclusion. This investigation identified the potent antibacterial agents against certain infections.